2023
DOI: 10.1177/21582440231162535
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Ownership and Ambivalent Employee Behaviors: A Moderated Mediation Model

Abstract: Prior studies regard psychological ownership as a positive thing, but this study suggested two faces of psychological ownership. Specifically, we focused on the psychological process wherein two different routes via disparate mediators led to two seemingly contradictory outcomes: organizational citizenship behavior (OCB) and workplace aggressive behavior (WAB). In addition, we also examined the moderating role of a structural factor (i.e., network position) in the mediation process. Drawing on the social excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it has been found that psychological ownership has effects on organizational citizenship behaviors and those can indirectly contribute to better job performance (A. J. Kim & Chung, 2023). It can be hypothesized that employees experiencing a sense of psychological ownership, aligning their individual goals with those of the organization, are more likely to improve their job performance.…”
Section: Safety Ownership Affective Commitment and Performancementioning
confidence: 99%
“…Moreover, it has been found that psychological ownership has effects on organizational citizenship behaviors and those can indirectly contribute to better job performance (A. J. Kim & Chung, 2023). It can be hypothesized that employees experiencing a sense of psychological ownership, aligning their individual goals with those of the organization, are more likely to improve their job performance.…”
Section: Safety Ownership Affective Commitment and Performancementioning
confidence: 99%